2011
DOI: 10.1007/978-3-642-21064-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Enrichment of Twitter Posts for User Profile Construction on the Social Web

Abstract: Abstract. As the most popular microblogging platform, the vast amount of content on Twitter is constantly growing so that the retrieval of relevant information (streams) is becoming more and more difficult every day. Representing the semantics of individual Twitter activities and modeling the interests of Twitter users would allow for personalization and therewith countervail the information overload. Given the variety and recency of topics people discuss on Twitter, semantic user profiles generated from Twitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 8 publications
2
145
0
2
Order By: Relevance
“…In particular, profiles are enriched with entities and topics extracted from news articles that are linked with Twitter messages. In previous work, we have done the study on selecting appropriate news articles for enriching tweets [12]. We revealed that for Twitter messages, which do not explicitly link to external Web resources we can find related news articles that report about the same event as the Twitter message with a high precision of more than 70%.…”
Section: Definition 1 (User Profile)mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, profiles are enriched with entities and topics extracted from news articles that are linked with Twitter messages. In previous work, we have done the study on selecting appropriate news articles for enriching tweets [12]. We revealed that for Twitter messages, which do not explicitly link to external Web resources we can find related news articles that report about the same event as the Twitter message with a high precision of more than 70%.…”
Section: Definition 1 (User Profile)mentioning
confidence: 99%
“…Rowe et al [11] proposed to exploit contextual information to enrich the semantics of Twitter messages. In previous work, we followed this suggestion and linked tweets to related Web resources [12]. Given this semantic enrichment, we proposed user modeling strategies that allow for recommending news articles.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] it had mentioned that usually Web sites allow interchange of information and let analyze collective behavior, because is hard analyze user individual information. That way is important the fact that users need to be linked in social networks, and it happened because they have some interests or characteristics in common.…”
Section: Frameworkmentioning
confidence: 99%
“…As will be commented in the next section, many researchers have focused on the analysis of hashtags in order to perform complex knowledge-based tasks on a corpus of tweets [12,13]. However, most of the scientific contributions have focused almost exclusively on a purely syntactic analysis of the content of tweets, including their hashtags.…”
Section: Introductionmentioning
confidence: 99%